2018
DOI: 10.1002/adma.201705112
|View full text |Cite
|
Sign up to set email alerts
|

Single Pt Atoms Confined into a Metal–Organic Framework for Efficient Photocatalysis

Abstract: It is highly desirable yet remains challenging to improve the dispersion and usage of noble metal cocatalysts, beneficial to charge transfer in photocatalysis. Herein, for the first time, single Pt atoms are successfully confined into a metal-organic framework (MOF), in which electrons transfer from the MOF photosensitizer to the Pt acceptor for hydrogen production by water splitting under visible-light irradiation. Remarkably, the single Pt atoms exhibit a superb activity, giving a turnover frequency of 35 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
448
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 698 publications
(459 citation statements)
references
References 56 publications
11
448
0
Order By: Relevance
“…Many works are being reported on this topic, but in many cases framework is destroyed by the electron beam making location of the incorporated species in the original material impossible. In this sense, Fang et al . reported the synthesis of single Pt atom catalyst for hydrogen production by water splitting under visible‐light irradiation, where C S ‐corrected STEM‐HAADF was used to characterize the dispersion and distribution of Pt atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Many works are being reported on this topic, but in many cases framework is destroyed by the electron beam making location of the incorporated species in the original material impossible. In this sense, Fang et al . reported the synthesis of single Pt atom catalyst for hydrogen production by water splitting under visible‐light irradiation, where C S ‐corrected STEM‐HAADF was used to characterize the dispersion and distribution of Pt atoms.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work of Jiang's group, they confined single Pt atoms into the highly stable aluminum‐based porphyrinic MOF. Infinite Al(OH)O 4 chains are interconnected by the porphyrin linkers into a 3D microporous framework, while Pt(II) metalated into the porphyrin centers …”
Section: Synthetic Methods Of Mof‐derived Carbon‐supported Sacsmentioning
confidence: 99%
“…The obtained single metal atom photocatalyst Al‐TCPP‐Pt showed an outstanding photocatalytic performance for hydrogen production, giving a turnover frequency of 35 h −1 , which was ≈30 times that of Pt nanoparticles stabilized by the same MOF. Ultrafast transient absorption spectroscopy and DFT calculations indicated that the confined single Pt atoms in Al‐TCPP opened a highly efficient electron transfer channel and improved the hydrogen binding energy, resulting in the enhanced photocatalytic H 2 production activity …”
Section: Application In Photocatalysismentioning
confidence: 99%